PERSEPSI SISWA PADA PEMBELAJARAN PJOK DI SMAN TARUNA NALA BERBASIS SEMI MILITER: ANTARA TANTANGAN, KELELAHAN, DAN MANFAAT - Taufiqi, Mochammad Alfan; Yudasmara, Dona Sandy; Trinopiansyah, Nade (Universitas Negeri Medan, 2024)
This study aims to explore students’ perceptions of Physical Education, Sports, and Health (PJOK) learning at SMAN Taruna Nala, a boarding school with a semi-military education system in East Java, Indonesia. Employing a quantitative approach through survey methods, the study involved 151 students from grades X and XI as respondents. A Likert-scale questionnaire was used to measure three main dimensions: enjoyment, challenges and fatigue, and benefits of PJOK learning. The results showed that students had a very positive perception regarding the enjoyment and benefits of PJOK, with average scores falling under the “Very Good” category. Meanwhile, the dimension of challenges and fatigue was categorized as “Fair,” indicating the presence of physical demands without significantly reducing students’ enthusiasm for PJOK. These findings suggest that despite the physically demanding and highly disciplined environment, students perceive PJOK as an enjoyable and meaningful subject that supports both physical and psychological development. The study highlights the importance of adaptive teaching approaches in PJOK, particularly in educational settings with unique characteristics such as semi-military schools.